Baseline study: Digital fisheries and scaling postharvest technologies to reduce aquatic food waste and loss in coastal Kenya - Manyise, Timothy; Brako Dompreh, Eric (2025)
The baseline study on Digital Fisheries and Scaling Postharvest Technologies to Reduce Aquatic Food Waste and Loss in Coastal Kenya provides a comprehensive dataset on the socio-economic characteristics, fisheries management practices, and postharvest challenges faced by fisherfolk and fish traders. Conducted across the coastal counties of Mombasa, Kwale, Kilifi, Lamu, and Tana River, this study employs a mixed-methods approach to assess the adoption of postharvest technologies, digital tools, access to resources and participation, and infrastructural gaps affecting fisheries productivity and fish loss and waste. The findings highlight critical barriers, including limited awareness of digital technologies, inadequate cold storage facilities, and financial constraints that contribute to significant postharvest losses. The dataset serves as a foundational resource for policymakers, researchers, and development practitioners seeking to enhance fisheries management, strengthen fisheries value chains, and promote sustainable aquatic food systems in Kenya’s coastal regions.